Radość ziemska i niebiańska w kulturze średniowiecza - KOBIELUS, Stanisław (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
According to medieval writers, there are many kinds and many causes of joy. Yet the fact that earthly existence has its beginning and its end was the source of the feeling that joy is merely provisional and that the permanence of happiness is thus threatened. As a result, perceived as limited in its nature, joy almost lost its significance. However, laughter was still considered to be an external manifestation of both earthly and heavenly joy. Moreover, even though St. Bridget of Sweden would write that there is little joy in the laughter that is surely to be followed by tears, rejoicing was found in this world even among the sufferings it inflicts on the human being, which conformed to the teachings of Christ (cf. Lk 6, 23). Both in the Old and in the New Testament, one can find descriptions of amusements, dances, banquets, and exultations, all of which were forms of rejoicing and demonstrated a joyful manner of being. Yet in medieval literature the emphasis was clearly shifted from the earthly matters to the spiritual ones, and solely spiritual joys, as opposed to their carnal counterparts, were considered as the source of full joy. Not infrequently though were earthly joys translated into heavenly ones, by way of enhancement and by being attributed the quality of permanence. In art, heavenly joy was promised in images of angels making music, depicted by painters, for instance, in compositions of the Final Judgment. According to some authors, once the human soul entered the glory of God, it was among angels and saints. Yet participation in this eschatological bliss was not considered easily accessible to everyone. The Book of Revelation says: “Outside are the dogs, the sorcerers, the unchaste, the murderers, the idol−worshipers, and all who love and practice deceit” (Apoc 22: 15). Translated by Dorota Chabrajska